Workable sisterhood : the political journey of stigmatized women with HIV/AIDS - Berger, Michele Tracy, 1968- (Princeton University Press, 2006)
Workable Sisterhood is an empirical look at sixteen HIV-positive women who have a history of drug use, conflict with the law, or a history of working in the sex trade. What makes their experience with the HIV/AIDS virus and their political participation different from their counterparts of people with HIV? Michele Tracy Berger argues that it is the influence of a phenomenon she labels "intersectional stigma," a complex process by which women of color, already experiencing race, class, and gender oppression, are also labeled, judged, and given inferior treatment because of their status as drug